2020
DOI: 10.1177/0011128719901109
|View full text |Cite
|
Sign up to set email alerts
|

Simplifying Reality: The Media’s Portrayal of the Private Prison Debate

Abstract: Although the media gives considerable attention to prison privatization, there have been few assessments of how newspapers portray the debate about it and how that portrayal aligns with what is known empirically about private prisons. This study addresses this gap in the literature by undertaking a content analysis of newspaper articles ( N = 131) about private prisons and private Immigration and Customs Enforcement facilities, respectively. The results show that few news stories discuss the broad range of fac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(10 citation statements)
references
References 54 publications
0
10
0
Order By: Relevance
“…Following the coding strategy of Montes et al. (2020), I also tracked whether specific frames were invoked explicitly or implicitly. Such a strategy responded to scholarship suggesting that news coverage tends to avoid explicit, nuanced discussions of matters relating to race and either class, wealth, and/or poverty (Bowman 2018; Kim et al.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Following the coding strategy of Montes et al. (2020), I also tracked whether specific frames were invoked explicitly or implicitly. Such a strategy responded to scholarship suggesting that news coverage tends to avoid explicit, nuanced discussions of matters relating to race and either class, wealth, and/or poverty (Bowman 2018; Kim et al.…”
Section: Resultsmentioning
confidence: 99%
“…Beyond the implications this study has for future research relating to higher education in prison, it also has potential implications relating to its conceptual design and methodology. As many have observed-most notably for the purposes of this study, Burkhardt (2014) and Montes et al (2020)-news media have a propensity to oversimplify debates relating to matters of criminal justice. Aligning with these findings, this study has demonstrated the lack of a fully nuanced moral framing of the debate within the media, as opposed to a much more frequently invoked (and more easily comprehended) instrumental framing.…”
Section: Limitations and Future Researchmentioning
confidence: 86%
See 2 more Smart Citations
“…Contemporary news articles perpetuate “traditional definitions of newsworthiness,” by centering around the “dangers of prison,” reinforcing stereotypes about prison, which paints incarceration as the primary solution to reducing crime ( Cecil, 2019 , p. 230). Reporting tends to oversimplify other salient topics (such as privatization of prisons), suggesting a disconnect between real life debates and their mediated coverage ( Cecil, 2017 ; Montes et al, 2020 ). Overall, media typically constructs prison populations as other – marginalized either through deviance or through absence.…”
Section: Prison Coverage In the News Mediamentioning
confidence: 99%